Analisis Pelayanan Bagasi Petugas Lost and Found PT Jasa Angkasa Semesta di Yogyakarta Internasional Airport - Rida Sukma Andaruni; Anita Nur Masyi’ah (Master Manajemen, 2025)
At Yogyakarta International Airport there is one unit, namely the Lost And Found unit where in this unit there are problems handled by Lost And Found officers, namely complaints about lost baggage at the previous station during Malaysia Airline flights when they arrive at the destination airport to pick up their baggage. This study aims to determine how Lost And Found officers deal with lost baggage, find out the obstacles faced by Lost And Found officers in dealing with lost baggage, and to find out the efforts made by officers to handle complaints from passengers. This study uses a qualitative method, where this study is descriptive and uses analysis by paying attention to inductive analysis. This study was conducted for four months from January to April 2025 at the Lost And Found Unit of PT Jasa Angkasa Semesta Maskapai Malaysia Airline at Yogyakarta International Airport. The data used in this study were in the form of interviews, observations, and documentation which were then supported by valid evidence, so that later they could be declared credible. The results of this study are the services of Lost And Found officers in handling lost baggage by officers making PIRs for passengers who lose their baggage, if the baggage is not found within 14 days, the officer can provide compensation in accordance with applicable regulations. The obstacles faced by Lost And Found officers in dealing with lost baggage are the limitations of human resources and language faced by officers. Efforts made by officers in handling complaints from passengers are that Lost And Found officers provide clear and precise information to passengers regarding the steps in handling baggage.